Design of River Tour Boat’s Hull For Taman Nasional Tanjung Puting, Central Borneo - Danu Utama; Ahmad Nasirudin; Muhammad Iqbal (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2020)
Tanjung Puting National Park is a natural wildlife park with a positively increasing trend in the number of visitors. The transportation which is utilized in Sekonyer river is ‘klotok’ boat, a traditional tour boat modified from a fishing boat. The design of a fiberglass-based tour boat is needed to accommodate the limitation of Kalimantan’s logs, which become the main structural components of klotok and to comply with the technical characteristic of the river. The purpose of this study is to obtain the optimum main dimensions of the fiberglass-based tour boat and its hull form design. The method performed to obtain the main dimension of the boat is non-linear optimization with the help of solver in Microsoft Excel software. The process of boat’s hull design is done by line distortion approach where the shape of a reference boat’s hull is conformed to a particular size and hydrodynamical coefficients, which are obtained from the optimization process. The result of optimization process is the main dimension of the boat (Lpp = 12.23 m, B = 2.70 m, H = 1.14 m, T = 0.80 m and Cb = 0.55). By conducting a series of calculations, the obtained value of the total boat’s resistance worths 2,427 N. Therefore, the number of boat’s power needed is less than the power of existing boats. The boat’s hull also complies with technical requirements and regulations, which are freeboard and intact stability.